Nanoparticle‐Based Formulations of Glycopeptide Antibiotics: A Means for Overcoming Vancomycin Resistance in Bacterial Pathogens? - Pothineni, Bhanu Kiran; Keller, Adrian (Advanced NanoBiomed Research)
Keywords: General Medicine

Effect of Ionic Strength on the Thermal Stability of DNA Origami Nanostructures - Hanke, Marcel; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Stability of DNA Origami Nanostructures in Physiological Media: The Role of Molecular Interactions - Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Entwicklung einer Methode zur Integration der Additiven Fertigung in die Serienproduktion am Beispiel des Lasersinterns - Kruse, Anne

Detecting Novelties with Empty Classes - Uhlemeyer, Svenja; Lienen, Julian; Hüllermeier, Eyke; Gottschalk, Hanno (arXiv:2305.00983)
For open world applications, deep neural networks (DNNs) need to be aware of previously unseen data and adaptable to evolving environments. Furthermore, it is desirable to detect and learn novel classes which are not included in the DNNs underlying set of semantic classes in an unsupervised fashion. The method proposed in this article builds upon anomaly detection to retrieve out-of-distribution (OoD) data as candidates for new classes. We thereafter extend the DNN by $k$ empty classes and fine-tune it on the OoD data samples. To this end, we introduce two loss functions, which 1) entice the DNN to assign OoD samples to the empty classes and 2) to minimize the inner-class feature distances between them. Thus, instead of ground truth which contains labels for the different novel classes, the DNN obtains a single OoD label together with a distance matrix, which is computed in advance. We perform several experiments for image classification and semantic segmentation, which demonstrate that a DNN can extend its own semantic space by multiple classes without having access to ground truth.

Aspects of a Sustainability Focused Comparison of the Wire Arc Additive Manufacturing (WAAM) and the Laser Powder Bed Fusion (LPBF) Process - Wurst, Johanna; Steinhoff, Timon; Mozgova, Iryna; Hassel, Thomas; Lachmayer, Roland

Concept and Implementation of a Student Design Project for the Development of Sustainable Products - Wurst, Johanna; Rosemann, Daniel; Mozgova, Iryna; Lachmayer, Roland

Structure–Reactivity Relationships in Borane-Based FLP-Catalyzed Hydrogenations, Dehydrogenations, and Cycloisomerizations - Paradies, Jan (Accounts of Chemical Research)
Keywords: General Medicine; General Chemistry

Wirtschaft neu ausrichten. Care-Initiativen in Deutschland, Österreich und der Schweiz.

Exergaming in older adults: the effects of game characteristics on brain activity and physical activity - Müller, Helen; Baumeister, Jochen; Bardal, Ellen Marie; Vereijken, Beatrix; Skjæret-Maroni, Nina (Frontiers in Aging Neuroscience)
Introduction Exergames are increasingly used in rehabilitation settings for older adults to train physical and cognitive abilities. To meet the potential that exergames hold, they need to be adapted to the individual abilities of the player and their training objectives. Therefore, it is important to know whether and how game characteristics affect their playing. The aim of this study is to investigate the effect of two different kinds of exergame (step game and balance game) played at two difficulty levels on brain activity and physical activity. Methods Twenty-eight older independently living adults played two different exergames at two difficulty levels each. In addition, the same movements as during gaming (leaning sideways with feet in place and stepping sideways) were performed as reference movements. Brain activity was recorded using a 64-channel EEG system to assess brain activity, while physical activity was recorded using an accelerometer at the lower back and a heart rate sensor. Source-space analysis was applied to analyze the power spectral density in theta (4 Hz–7 Hz) and alpha-2 (10 Hz–12 Hz) frequency bands. Vector magnitude was applied to the acceleration data. Results Friedman ANOVA revealed significantly higher theta power for the exergaming conditions compared to the reference movement for both games. Alpha-2 power showed a more diverse pattern which might be attributed to task-specific conditions. Acceleration decreased significantly from the reference movement to the easy condition to the hard condition for both games. Discussion The results indicate that exergaming increases frontal theta activity irrespective of type of game or difficulty level, while physical activity decreases with increasing difficulty level. Heart rate was found to be an inappropriate measure in this population older adults. These findings contribute to understanding of how game characteristics affect physical and cognitive activity and consequently need to be taken into account when choosing appropriate games and game settings for exergame interventions.
Keywords: Cognitive Neuroscience; Aging

Learning Computational Thinking in Secondary School (Year 8) in Germany in International Comparison: Results from ICILS 2018 - Labusch, Amelie; Eickelmann, Birgit (Teaching coding in K-12 schools: Research and application)

Die inhaltliche Ausgestaltung schulischer Medienkonzepte als Gelingensbedingung digitalisierungsbezogener Schulentwicklungsprozesse - Schulze, Johanna; Drossel, Kerstin; Eickelmann, Birgit (Professionalisierung für digitale Bildung im Grundschulalter - Ergebnisse des Forschungsprojekts P3DiG)

Digitalisierungsbezogene Schulentwicklungsprozesse erfolgreich gestalten. Handreichung für die schulische Arbeit zu den Ergebnissen des Forschungsprojekts GuTe DigiSchulen NRW. - Gerick, J.; Eickelmann, Birgit; Rau, M.; Panten, B.; Rothärmel, A.; Gottschalk, T.

Optimization of inductive fast-curing of epoxy adhesive by model-based kinetics - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (International Journal of Adhesion and Adhesives)

Simulation des „viscous fingering“ Effektes in Klebverbindungen - Salten, Alexander Heinrich Johannes; Al Trjman, Mohamad; Meschut, Gerson; Kenig, Eugeny Y.

Methodenentwicklung zur Simulation des Viscous Fingering in Klebverbindungen von stahlintensiven Mischbaustrukturen - Al Trjman, Mohamad; Meschut, Gerson; Salten, Alexander Heinrich Johannes; Kenig, Eugeny Y.

Model-based condition monitoring of piezoelectric bending actuators - Bender, Amelie (Sensors and Actuators A: Physical)
With enhancing digitalization, condition monitoring is used in an increasing number of application fields across various industrial sectors. By its application, increased reliability as well as reduced risks and costs can be achieved. Based on different approaches, technical systems are monitored and measured data is analyzed to enable condition-based or predictive maintenance. To this end, machine learning approaches are usually implemented to diagnose the health states or predict the health index of the monitored system. However, these trained models are often black-box models, not intuitively explainable for a human. To overcome this shortcoming, a model-based approach based on physics is developed for piezoelectric bending actuators. Such a model enables a transparent representation of the system. Moreover, the model-based approach is extended by a parameter-estimation to account for sudden changes in behavior e. g. caused by occurring cracks.
Keywords: Condition Monitoring; Model-based approach Diagnostics; Varying conditions; Explainability; Piezoelectric bending actuators

Resilient Requirements Engineering - Gräßler, Iris; Oleff, Christian; Preuß, Daniel; Koch, Anna-Sophie (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Entwicklungsprojekte stehen in einem Spannungsfeld von Volatilität, Unsicherheit, Komplexität und Ambiguität (VUCA). Resilient Requirements Engineering (RRE) ist ein vielversprechender Ansatz, diesen Rahmenbedingungen gerecht zu werden und erfolgreich zu entwickeln. Es werden Methoden aus den drei Innovationsfeldern des RRE – Vorausschau, Effizienz und Nachhaltigkeit – angewendet, um Effizienzpotenziale in der Produktentwicklung zu nutzen und frühzeitig Nachhaltigkeitsdimensionen in der Ermittlung von Stakeholderbedürfnissen zu verankern.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

MAAS: Hiding Trojans in Approximate Circuits - Ahmed, Qazi Arbab; Awais, Muhammad; Platzner, Marco (The 24th International Symposium on Quality Electronic Design (ISQED'23), San Francisco, Califorina USA)

Minimum Edge Cuts in Overlay Networks - Schweichhart, Jonas